Current status of minimally invasive surgery for gastric cancer: A literature review to highlight studies limits. (May 2015) - Parisi, Amilcare; Nguyen, Ninh T.; Reim, Daniel; Zhang, Shu; Jiang, Zhi-Wei; Brower, Steven T.; Azagra, Juan-Santiago; Facy, Olivier; Alimoglu, Orhan; Jackson, Patrick G.; Tsujimoto, Hironori; Kurokawa, Yukinori; et al.
Abstract: Background: Gastric cancer represents a great challenge for health care providers and requires a multidisciplinary approach in which surgery plays the main role. Minimally invasive surgery has been progressively developed, first with the advent of laparoscopy and more recently with the spread of robotic surgery, but a number of issues are currently being investigate, including the limitations in performing effective extended lymph node dissections and, in this context, the real advantages of using robotic systems, the possible role for advanced Gastric Cancer, the reproducibility of completely intracorporeal techniques and the oncological results achievable during follow-up. Method: Searches of MEDLINE, Embase and Cochrane Central Register of Controlled Trials were performed to identify articles published until April 2014 which reported outcomes of surgical treatment for gastric cancer and that used minimally invasive surgical technology. Articles that deal with endoscopic technology were excluded. Results: A total of 362 articles were evaluated. After the review process, data in 115 articles were analyzed. Conclusion: A multicenter study with a large number of patients is now needed to further investigate the safety and efficacy as well as long-term outcomes of robotic surgery, traditional laparoscopy and the open approach. Highlights: Minimally invasive surgery has been developed in last years. Patients with gastric cancer could benefit from this approach. A multi-institutional study is needed.